1978
DOI: 10.1080/00039896.1978.10667299
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among Individuals Occupationally Exposed to Benzene

Abstract: The mortality experience of 594 individuals occupationally exposed to benzene was investigated using a retrospective cohort design. Three hundred thirty-five of the employees began working in benzene areas prior to 1950, which provided a sound data base from which to examine latency. Data derived from work histories and industrial hygiene records permitted estimation of exposure intensities and cumulative dosages for each employee. No mortalities directly attributable to benzene exposure were observed. Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(89 citation statements)
references
References 0 publications
3
85
1
Order By: Relevance
“…The WHO Office also calculated the unit risk as 3.8 X 10-6 with the same model based on the reports of Ott et al 48) and Bond et al 49) concerning the Dow Chemical cohort by assuming that the SMR of myeloleukemia was 4.40, the background death rate from the leukemia 0.003 for life, the benzene exposure level in the cohort was 100 mg/m3, and the exposure period was 8.5 years. On the basis of these values, the WHO Office proposed a value of 4 X 10 6 as the unit risk for leukemia of benzene in the environmental atmosphere.…”
Section: Biological Monitoring Of Benzene Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The WHO Office also calculated the unit risk as 3.8 X 10-6 with the same model based on the reports of Ott et al 48) and Bond et al 49) concerning the Dow Chemical cohort by assuming that the SMR of myeloleukemia was 4.40, the background death rate from the leukemia 0.003 for life, the benzene exposure level in the cohort was 100 mg/m3, and the exposure period was 8.5 years. On the basis of these values, the WHO Office proposed a value of 4 X 10 6 as the unit risk for leukemia of benzene in the environmental atmosphere.…”
Section: Biological Monitoring Of Benzene Exposurementioning
confidence: 99%
“…In addition, the exposure group had no case of acute myeloic leukemia, which is known to be strongly associated with benzene, among the cases of death due to leukemia. While Ott et al 48) examined three cases of leukemia occurring among 594 workers exposed to benzene in 33 years (1940-1973), those exposed to benzene were also exposed to various other chemical compounds.…”
Section: Benzene Metabolism According To Exposure Concentrationmentioning
confidence: 99%
“…Benzene induced both solid tumors and leukemias in rats exposed by gavage (Mattoni et al 1985). Many studies have also described a causal relationship between exposure to benzene by inhalation (either alone or in combination with other chemicals) and leukemia in humans (lARC 1982, Rinsky et al 1981, Ott et al 1978, Wong et al 1983.…”
Section: Benzenementioning
confidence: 99%
“…EPA (1990) derived both an oral and an inhalation cancer potency factor for benzene of 2.9x10"^ (mg/kg-day)■^ This value was based on several studies in which increased incidences of nonlymphocytic leukemia were observed in humans occupationally exposed to benzene principally by inhalation (Rinsky et al 1981, Ott et al 1978, Wong et al 1983. is currently reviewing both oral and inhalation RfDs for benzene, for which the status is pending.…”
Section: Benzenementioning
confidence: 99%
“…In Table 2 criteria for arsenic and benzene have been derived directly from available human carcinogenic data (57)(58)(59)(60). Neither compound has been shown to produce carcinogenic response in experimental animals.…”
Section: Examples Of Proposed Criteriamentioning
confidence: 99%